Mechanical signatures of microbial biofilms in micropillar-embedded growth chambers. Issue 23 (18th May 2016) - Chew, S. C.; Kundukad, B.; Teh, W. K.; Doyle, P.; Yang, L.; Rice, S. A.; Kjelleberg, S.
Abstract : Biofilms are surface-attached communities of microorganisms embedded in an extracellular matrix and are essential for the cycling of organic matter in natural and engineered environments. Abstract : Biofilms are surface-attached communities of microorganisms embedded in an extracellular matrix and are essential for the cycling of organic matter in natural and engineered environments. They are also the leading cause of many infections, for example, those associated with chronic wounds and implanted medical devices. The extracellular matrix is a key biofilm component that determines its architecture and defines its physical properties. Herein, we used growth chambers embedded with micropillars to study the net mechanical forces (differential pressure) exerted during biofilm formation in situ . Pressure from the biofilm is transferred to the micropillars via the extracellular matrix, and reduction of major matrix components decreases the magnitude of micropillar deflections. The spatial arrangement of micropillar deflections caused by pressure differences in the different biofilm strains may potentially be used as mechanical signatures for biofilm characterization. Hence, we submit that micropillar-embedded growth chambers provide insights into the mechanical properties and dynamics of the biofilm and its matrix.